Stratigraphy and depositional environment of the Horton Group in the St Marys Basin, central mainland Nova Scotia - Murphy, J.; Rice, Randolph (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1998)
The St. Marys Basin, central mainland Nova Scotia, contains an Upper Devonian(?)-Lower Carboniferous intracontinental alluvial fan-fluviatile-lacustrine basin-fill sequence that occupies the current boundary between the Meguma and Avalon terranes of the Canadian Appalachian orogen. The basin rocks belong to the Horton Group, and are here divided into six partially laterally equivalent formations. The stratigraphically lowest rocks are predominantly exposed in the central part of the basin in a series of en echelon anticlinal closures. These rocks were deposited in a longitudinal drainage system and represent clastic strata deposited in lacustrine (Little Stewiacke River Formation) and braided fluvial (Barrens Hills and Lochiel formations) environments. Toward the southern flank of the basin the sequence is essentially a southeast-facing monocline in which the beds coarsen and thicken upward. Along this flank, clastic rocks were predominantly deposited in alluvial fans (Cross Brook and West River St Marys formations) derived from the Meguma terrane to the south. These rocks unconformably overly the Meguma Group, reflecting a decrease in accommodation space and implying that the St. Marys Basin is underlain, at least in part, by Meguma basement. In the northwestern part of the basin, clastic sedimentary rocks have mixed Avalonian-Meguma provenance (Graham Hill Formation) reflecting influence of the Avalonian margin to the north and confirming the status of the Horton Group as a post-Acadian overstep sequence. The deposition of coarse conglomerate along the southern flank of the basin suggests a strong tectonic influence on sedimentation where subsidence along this basin margin occurred along northerly dipping listric normal faults. In contrast, the character of the sediments does not vary with proximity to the northern margin of the basin (Chedabucto Fault), suggesting that the fault does not constitute the original basin margin, and that an unknown portion of the basin and its Meguma basement have been tectonically removed.